Ethanol-mediated carcinogenesis in the human esophagus implicates CYP2E1 induction and the generation of carcinogenic DNA-lesions - Millonig, Gunda; Wang, Ying; Homann, Nils; Bernhardt, Friederike; Qin, Hua; Mueller, Sebastian; Bartsch, Helmut; Seitz, Helmut K. (International journal of cancer, 2011)
Chronic alcohol consumption is a major risk factor for esophageal cancer. Various mechanisms may mediate carcinogenesis including the genotoxic effect of acetaldehyde and oxidative stress. Ethanol exerts its carcinogenic effect in the liver among others via the induction of cytochrome P450 2E1 (CYP2E1) and the generation of carcinogenic etheno-DNA adducts. Here we investigated if such effects can also be observed in the human esophagus. We studied nontumorous esophageal biopsies of 37 patients with upper aerodigestive tract cancer and alcohol consumption of 102.3 ± 131.4 g/day (range: 15-600 g) as well as 16 controls without tumors (12 teetotalers and 4 subjects with a maximum of 25 g ethanol/day). CYP2E1, etheno-DNA adducts and Ki67 as a marker for cell proliferation were determined immunohistologically. Chronic alcohol ingestion resulted in a significant induction of CYP2E1 (p = 0.015) which correlated with the amount of alcohol consumed (r = 0.6, p < 0.001). Furthermore, a significant correlation between CYP2E1 and the generation of the carcinogenic exocyclic etheno-DNA adducts 1,N6-ethenodeoxyadenosine (r = 0.93, p < 0.001) and 3,N4-ethenodeoxycytidine (r = 0.92, p < 0.001) was observed. Etheno-DNA adducts also correlated significantly with cell proliferation (p < 0.01), which was especially enhanced in patients who both drank and smoked (p < 0.001). Nonsmokers and nondrinkers had the lowest rate of cell proliferation, CYP2E1 expression and DNA lesions. Our data demonstrate for the first time an induction of CYP2E1 in the esophageal mucosa by ethanol in a dose dependent manner in man and may explain, at least in part, the generation of carcinogenic DNA lesions in this target organ.